The Efficiency of Beauveria bassiana, Metarhizium anisopliae and Lecanicillium muscarium against different stages of the flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - Al-Zurfi, Sienaa; A. Kareem, Ali; T. Alamry, Alaa; Jawad Kadhem, Zahraa; Port, Gordon; Sanderson, Roy (Journal of Kerbala for Agricultural Sciences, 2023)
This study evaluated the efficacy of commercial formulations of Metarhizium anisopliae, Beauveria bassiana and Lecanicillium muscarium against different stages of T. castaneum. All commercial formulations were tested against the insects using a topical spray under laboratory conditions. Insects were sprayed with conidial concentration 3 × 108 conidia/ml of B. bassiana or M. anisopliae and 2 × 107 conidia/ml of L. muscarium. Mortality was recorded daily for seven days while insects were kept on wheat flour. All commercial formulationsshowed an effect on T. castaneum; however, B. bassiana and M. anisopliae were more effective than L. muscarium at the concentrations tested. However, susceptibility showed significant differences in percentage mortality at the end of the experiments between first, third, and sixth instar larvae and adults treated with all three commercial formulations. First and third-instar larvae were most susceptible, and sixth-instar larvae and adults were least vulnerable to infection. In all experiments, the temperature had no significant effect on insect mortality caused by B. bassiana, M. anisopliae, and L. muscarium. There was a small difference in the insect mortality level for each fungus between 25°C and 30°C. All fungi were slightly, but not significantly, more effective at 25°C. The strains of all fungi tested caused significant mortality of T. castaneum by contact.